Impact evaluation of "Have Fun — Be Healthy" program: A community based health promotion intervention to prevent childhood obesity. (28th December 2017) - Pathirana, Thanya; Stoneman, Rebecca; Lamont, Amanda; Harris, Neil; Lee, Patricia
Abstract: Issue addressed: Childhood obesity is rising in prevalence in Australia. This study aimed to evaluate the impact of the "Have Fun—Be Healthy" (HFBH) intervention, delivered in the Playgroup setting, to generate short term changes in dietary, physical activity and sedentary behaviours of children under 5 years and self‐efficacy of parents and primary carers. Methods: This intervention consisted of eight structured cooking and physical play sessions delivered over a period of 8 weeks by trained facilitators. Pre‐ and post‐intervention data collection was performed using survey questionnaires administered to parents and carers of children under 5 years from low socioeconomic backgrounds recruited through convenience sampling. Results: A total of 640 pre‐intervention surveys and 312 post‐intervention surveys were returned. The matched response rate was 45.5%. There was an improvement in mean intake of healthy foods and mean physical activity with a decrease in mean intake of unhealthy food and mean screen time in children ( P > .05). Following the intervention, parental/carer self‐efficacy in promoting healthy eating and limiting screen time of children improved significantly ( P < .05). Children's physical activity levels and consumption of healthy foods were positively correlated with parental/carer self‐efficacy ( P < .01) while screen time and consumption of unhealthy foods were negatively correlated ( P < .01). Conclusions: HFBH intervention was successful in improving the dietary, physical activity and screen time in children and parental self‐efficacy. So what?: Being amongst the first of its' kind in Australia, the findings of this study can have implications for developing and implementing similar future health promotion interventions in comparable settings.